2019
DOI: 10.1108/hcs-10-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Southern European welfare states and homelessness: Portugal and Greece

Abstract: Purpose The purpose of this paper is to compare homelessness policies in Portugal and Greece. Design/methodology/approach After a brief overview of the relationship between welfare regimes and homelessness, the characteristics of homelessness policies within the South-European regime are studied. Subsequently, by employing empirical data, a comparison between the homelessness policies of these two countries is attempted through three axes of analysis: the historical emergence of homelessness policies; the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…When this takes place in the years of a crisis, it leads to a double negative consequence. While housing problems are being exacerbated, housing support measures, which are poor in any case, are being reduced even further (Kourachanis, 2019). This fact has been discussed in previous studies, which take the urban environment as their starting point (for example, Arapoglou and Gounis, 2017;Papadopoulou and Kourachanis, 2017).…”
Section: Residual Public Housing Interventionsmentioning
confidence: 95%
“…When this takes place in the years of a crisis, it leads to a double negative consequence. While housing problems are being exacerbated, housing support measures, which are poor in any case, are being reduced even further (Kourachanis, 2019). This fact has been discussed in previous studies, which take the urban environment as their starting point (for example, Arapoglou and Gounis, 2017;Papadopoulou and Kourachanis, 2017).…”
Section: Residual Public Housing Interventionsmentioning
confidence: 95%
“…In 2022, in the region of Attica, 76% of tenants, after covering housing costs, had to either limit other essential expenses or rely on financial support from third parties (Eteron, 2022a, b, c). Moreover, 76,9% of young people (18 to 34) are hosted by their parents (Eurostat, 2021a, b), while the population of homeless people has increased (Kourachanis, 2019). Finally, rent prices in central Athenian districts in Europe concerning the fastest amortization of real estate investment, as it takes just 17.66 years for the original investment to be amortized (Kathimerini, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has also shown that as the number of people in extremely precarious living situations rises, few are managing to break the cycle and move into regular housing [3]. This may be due to the multifactorial nature of homelessness [4][5][6][7] as well as a lack of political focus on addressing the causes of homelessness within national policies [8,9]. The phenomenon of living in temporary accommodation has been termed the "paradox of chronic emergency" [10].…”
Section: Introductionmentioning
confidence: 99%
“…Providing basic needs for this population, such as a roof or food, is essential but is also insufficient. Social rehabilitation can only be effective when the biopsychosocial causes of homelessness are also addressed [8,9,11].…”
Section: Introductionmentioning
confidence: 99%